Moving beyond western methods: a methodological toolbox for family entrepreneurship research in tourism by including children's voices - Ju, Xiaoxi; Wengel, Yana; Schänzel, Heike; Liu, Claire (Frontiers in Sustainable Tourism, 2024)
Recently, tourism scholars turned their attention to families, specifically children's experiences. Yet, research illustrating children's voices in tourism family entrepreneurship is missing. Social researchers are encouraged to include children's voices to reveal their lived experiences rather than considering them too vulnerable to be interviewed. This qualitative study, underpinned by constructivist epistemology, explored how families are embedded within lifestyle migration and the tourism entrepreneurial process on Hainan Island in China. A combination of methods was adopted to create a toolbox suitable for family research, including children's voices through whole-family interviews and LEGO® Serious Play® workshops. Playing LEGO® seriously ensures that the researcher does not drive participants' thoughts, and children can freely express their opinions in playful, metaphorical, and meaningful ways. Moving beyond Western-centered methods, data was collected at Old Dad Teahouses (or Lao Ba Cha 老爸茶 in Chinese) to create a friendly environment. Old Dad Teahouses are a Hainanese cultural ritual where locals gather to enjoy tea along with local savory snacks. Historically, the name Old Dad Tea refers to predominantly male customers over 50 years of age who regularly attended tea houses in the afternoon as part of their leisure. Nowadays, people who go to Old Dad Tea are more diverse in age and gender, and spending time there represents a popular leisure activity among families living in Hainan. We emphasize that our methodological toolbox allows us to explore how individuals construct their understanding through their own belief systems and culture. The methodological toolbox allowed us to understand the scholarship on family tourism entrepreneurship from a Chinese cultural perspective by providing insight into the experiences of 15 children from eight entrepreneurial families, providing agency to the children. This study aims to enrich the definition of family entrepreneurship by identifying how children as family members can influence migration and entrepreneurial behaviors and exploring the experiences gained by children through the entrepreneurial process. Children's voices are usually filled by adults within the family business unit. However, children are also rights holders and social agents. This study supports the right of children to participate and have their voices heard.